Pulmonary embolism—a long-term follow-up. Issue 678 (April 1982) - MacIntyre, D.; Banham, S. W.; Moran, F.
Abstract : Fifty-three patients without pre-existing cardiac or pulmonary disease were reviewed 5 to 9 years after angiographically proved pulmonary embolism. Ten of the 42 (24%) with an initial predisposing factor for embolism had died, including 6 from a previously diagnosed medical condition. In this group there was no significant residual disability among survivors and no late recurrence of embolism. By comparison, there were 6 deaths among the 11 in whom no predisposing factor was identified (55%), including 3 from neoplasm and 2 from recurrent embolism with cardiac failure. The identification of a predisposing factor at the time of embolism was associated with a significantly better long-term prognosis.